A methyltransferase LaeA regulates ganoderic acid biosynthesis in Ganoderma lingzhi - Luo, Qin; Li, Na; Xu, Jun-Wei (Frontiers in Microbiology, 2022)
The methyltransferase LaeA is a global regulator involved in the biosynthesis of secondary metabolites by ascomycete fungi. However, little is known of its regulatory role in basidiomycete fungi. In this study, the laeA gene was identified in the basidiomycete Ganoderma lingzhi and its function in regulating the biosynthesis of anti-tumor ganoderic acids was evaluated. A laeA deletion (ΔlaeA) Ganoderma strain exhibited significantly reduced concentration of ganoderic acids. qRT-PCR analysis further revealed that the transcription levels of genes involved in the biosynthesis of ganoderic acids were drastically lower in the ΔlaeA strain. Moreover, deletion of laeA resulted in decreased accumulation of intermediates and abundances of asexual spores in liquid static culture of G. lingzhi. In contrast, constitutive overexpression of laeA resulted in increased concentration of ganoderic acids. These results demonstrate an essential role of LaeA in the regulation of ganoderic acid biosynthesis in Ganoderma.